Answer:
8.
![y=-(7)/(3)(x-1)+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/swsdzira3br4mnylt8pekt8wyulzt83rjf.png)
9.
![y=(4)/(7)(x-2)-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jn5r9hnul97yrvr2oeh71u0w5u8qbcdt40.png)
10.
![y=-(3)/(4)x+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jdm4cmvce9vhzbq84p6kj5zgwcr6paikcy.png)
Explanation:
The equation of a line passing through points
and
is given as:
![y-y_(1)=((y_(2)-y_(1))/(x_(2)-x_(1)))(x-x_(1))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j45a31ghnyofth8qozcn7vhk9ut4y3mx1y.png)
For #8:
is
and
is
.
Now, plug in these values and find the equation of the line. This gives,
![y-5=((-2-5)/(4-1))(x-1)\\y-5=((-7)/(3))(x-1)\\y=-(7)/(3)(x-1)+5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6icixet6535c7b5u2s4ev2krj0bug9xlfr.png)
Therefore, the equation of a line passing through
and
is
.
For #9:
is
and
is
.
Now, plug in these values and find the equation of the line. This gives,
![y-(-1)=((-5-(-1))/(-5-2))(x-2)\\y+1=(-5+1)/(-7)(x-2)\\y+1=((-4)/(-7))(x-2)\\y=(4)/(7)(x-2)-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q42uflyqa7v8gj6p0d2jf8kmahuuo3371x.png)
Therefore, the equation of a line passing through
and
is
.
For #10:
is
and
is
.
Now, plug in these values and find the equation of the line. This gives,
![y-3=((0-3)/(4-0))(x-0)\\y-3=((-3)/(4))(x)\\y=-(3)/(4)x+3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u36cal4hb8io8sbz2dd1rrgmiebhpl40iv.png)
Therefore, the equation of a line passing through
and
is
.